“Hume Sweet Hume”: skepticism, idealism, and burial in Finnegans wake - Barlow, Richard Alan (2014)
What is the relationship between the Irish modernist writings of James Joyce and the Scottish empirical philosophy of David Hume? Here I discuss Joyce’s conception of Hume as a philosopher and explore the presence of Hume’s work in Joyce’s final masterpiece, Finnegans Wake. How then did Joyce conceive of Hume’s thought, and to what extent did he engage with it? Well, in his lecture “Realism and Idealism in English Literature,” given at Trieste in 1912, Joyce denounces the interest in the sanity (or otherwise) of artistic and philosophical geniuses, before offering the following comments: